ChemInform Abstract: Mixed AggregAte (MAA): A Single Concept for All Dipolar Organometallic Aggregates. 2. Syntheses and Reactivities of Homo/HeteroMAAs. Issue 48 (26th November 2013) - Mongin, Florence; Harrison‐Marchand, Anne
Abstract Review: 1708 refs.